PENGARUH KARAKTERISTIK KOMITE AUDIT, KARAKTERISTIK PERUSAHAAN DAN KOMPENSASI DEWAN TERHADAP KOMITE MANAJEMEN RISIKO (Studi pada Perusahaan Non Financial yang Terdaftar di BEI Tahun 2010-2012) - Vianika Herlantu; Andri Prastiwi (Diponegoro Journal of Accounting, 2014)
This study aimed to examine the association between Audit Committee characteristics, firm characteristics, compensation of Board to the Risk Management Committee. Risk Management Committee is the existence of RMC in the company, whether incorporated in or separate from the audit committee and independent Audit Committee. The variables examined in this study are the characteristics of an Audit Committee comprised of Audit Committees, accounting and financial expertise of the Audit Committee, Audit Committee size , the frequency of Audit Committee meetings, as an independent variable. In addition, the independent variables representing the characteristics of the company is the risk of financial reports and other independent variable is the compensation of the Board. Factors such as firm size, leverage, complexity of firm, and auditor reputation as a control variable is also examined in this study . This study used purposive sampling method to non-financial companies listed on the Indonesia Stock Exchange in 2010 until 2012. Logistic regression was used as a test of the hypothesis in this study and there are 288 samples used non-financial companies . The results of this study indicate that the size and frequency of meetings of the Audit Committee significantly and positively related to the Risk Management Committee, while, the accounting and financial expertise of the Audit Committee, the risk of the financial statements, the compensation Board and all the control variables no significant effect on the Risk Management Committee.